Results of application of organomineral fertilizer obtained with biocatalytic processes - E. B. Nikitin; L. I. Proskurina; A. N. Belov; B. A. Sharov; T. I. Uryumceva (Овощи России)
Relevance. The results of a study on the use of organomineral fertilizers obtained using biocatalytic processes for detoxification of poultry waste and their influence on the growth and development of plants during the growing season are presented.Methodology. For poultry farms, it is necessary to create and introduce waste-free technologies for the preparation of fertilizers. To increase the efficiency of the fertilizer as a biological catalyst, we used a bacterial growth stimulator sodium humate, obtained by us according to a previously developed technology from brown coal from the Maikubenskoye deposit in the Republic of Kazakhstan («Method for producing sodium humate» Patent No. 4600 RK), as well as a sorbent based on sodium humate (a by-product of obtaining sodium humate), which was used to detoxify the feedstock and the resulting product from heavy metals and their salts due to its absorption-adsorption and complexing properties. For the developed technology for producing organic fertilizers, an application has been submitted for obtaining a Patent for the invention of the Republic of Kazakhstan «Method for producing organic fertilizers» (priority No. 2021-22818, dated July 13, 2021). Studies to determine the effectiveness of the resulting fertilizer were carried out on the experimental plots of the peasant farm «Flame», Pavlodar district of Pavlodar region of the Republic of Kazakhstan. In the soil intended for growing seedlings of tomatoes of the «Pepper-shaped Orange» variety and peppers of the «Bogatyr» variety, the resulting fertilizer was applied in an amount of 1 kg per 1 m2 of soil, which was dug to a depth of 8-10 cm and used for growing seedlings in greenhouses and in subsequent for planting it in open ground. xperimental and control studies were carried out under equivalent climatic conditions, scheme and technology of watering plants. In total, 100 bushes of each plant species were used in the experiment.Results. The use of the obtained organomineral fertilizer makes it possible to increase the yield of vegetable crops (tomatoes, peppers) by 20-25% in comparison with the control. In addition, in the experimental samples, an increase in the number of fruits on the bush was noted with an increase in their size, a decrease in the growing season and the number of damaged fruits.